Elucidating the mechanism behind and investigating the efficacy of Traditional Chinese Medicine and Traditional Tibetan Medicine in combination with standard therapeutics in hepatocellular carcinoma and cholangiocarcinoma in vitro - Huizhen Suo; Inga Hochnadel; Nataliia Petriv; Raimo Franke; Jennifer Schmidt; Nataliia Limanska; Nataliia Limanska; Alisa Tugai; Nils Jedicke; Mark Broenstrup; Mark Broenstrup; Michael P. Manns; et al. (Frontiers Media S.A., 2022)
In this study, we investigated compounds of plant and mushroom origin belonging to Traditional Chinese Medicine (TCM) and to Traditional Tibetan Medicine (TTM): a sandy beige mushroom Trametes robiniophila Murr, commonly known as Huaier/TCM as well as Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan, which both belong to TTM. We aimed to study the efficacy of TTM and TCM in hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) in vitro. TCM and TTM were tested either as a monotherapy, or in combination with standard therapeutics: sorafenib for HCC treatment and gemcitabine for CCA. We also discovered a protective mechanism behind the most successful therapeutic combinations. The results demonstrated that TCM and TTM inhibited the proliferation of cancer cells in a time- and dose-dependent manner. The results were compared to classical chemotherapeutics currently used in the clinic: sorafenib for HCC and gemcitabine for CCA. In HCC settings, a combination of Huaier (16 mg/ml) with half of the human plasma concentration of sorafenib, Qiwei Honghua Shusheng Wan (1 mg/ml) monotherapy as well as its combination with half or even a quarter dose of the human plasma concentration of sorafenib represented the most efficient treatments, inhibiting the growth of HCC cells more effectively than the standard therapy. The inhibitory mechanism relied on a strong induction of apoptosis. In CCA settings, Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan as monotherapies or in combination with very low doses of gemcitabine inhibited the growth of CCA cells more efficiently than the standard therapy. Importantly, Ershiwuwei Songshi Wan at the 8 and 16 mg/ml concentrations and Qiwei Honghua Shusheng Wan at the 4 mg/ml concentration were efficacious with gemcitabine applied at massively reduced concentrations. The protective mechanism in CCA relied on a strong induction of early and late apoptosis. Cellular senescence and necroptosis were not associated with protection against HCC/CCA. Combination therapy with TCM or TTM allowed for a dose reduction of standard chemotherapeutics. This is especially important as both chemotherapeutic drugs show strong side effects in patients. The reduction of chemotherapeutics and the synergistic effect observed while applying them in combination with TCM and TTM has strong perspectives for the clinic and patients suffering from HCC and CCA.